Rural Landowners, Energy Leasing, and Patterns of Risk and Inequality in the Shale Gas Industry1. (9th August 2018) - Bugden, Dylan; Stedman, Richard
Abstract: Landowners who lease property for shale gas development (i.e., "fracking") face the possibility of procedural disenfranchisement and risk. They also stand to benefit financially from bonus and royalty payments. This article evaluates the frequency with which these experiences occur and how they vary between landowners. Using a mixed‐methods approach, we combine surveys and interviews with northeastern Pennsylvania landowners with a content analysis of energy lease documents. We find that landowners generally experience relatively infrequent environmental harm, receive substantial financial benefits, and leverage their property rights to secure better lease conditions. However, our findings also demonstrate that procedural disenfranchisement does occur, environmental risks are infrequent but real, and outcomes tend to vary by firm‐specific rather than sociostructural factors. Accordingly, the advantages conferred by private property are not a panacea for the alleviation of risk and inequality in energy development. These findings inject considerable nuance into ongoing discussions of risk, inequality, and shale gas development: Rather than perceiving themselves as victims, landowners tend to see themselves as beneficiaries of industry activity, an experience structured directly by their ownership of property and mineral rights.